Implementation of Child-Friendly Villages in Karawaci District, Tangerang City - Sindy Willys; Listyaningsih; Agung Satrio Wicaksono (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Fulfillment of children's rights in Indonesia still faces challenges marked by high cases of violence against children despite the implementation of various child protection policies, including the Child-Friendly Village Program (KRA). This study aims to analyze the implementation of the Child-Friendly Village Program in Karawaci District, Tangerang City using the Van Meter and Van Horn policy implementation model. The study uses a qualitative approach with descriptive methods. Research informants were selected through purposive and snowball sampling techniques involving elements of the Tangerang City DP3AP2KB, sub-district and village governments, Child-Friendly Village administrators, the Children's Forum, and the Karawaci District community. The research instrument was the researcher with data collection techniques in the form of observation, interviews, documentation, and literature studies. Data analysis used the Miles, Huberman, and Saldana models with validity tests through triangulation and member checks. The results of the study indicate that the implementation of the Child-Friendly Village Program has been running quite well in terms of policy dimensions and objectives, human resources, implementer characteristics, disposition, communication, and social environment, but still faces obstacles in the form of limited infrastructure, weak monitoring, suboptimal coordination, and low compliance with operational standards. This study concludes that the implementation of the Child-Friendly Village Program has supported child protection efforts, but the effectiveness of the program still requires strengthening in the aspects of supervision, cross-sector coordination, provision of child-friendly facilities, and increased community participation